A novel synthetic approach for designing metal-free, redox-active quinoxaline-benzimidazole-based organic polymers with high energy storage capacity. (4th September 2019) - Salunkhe, Pravin S.; Patil, Yuvraj S.; Dhole, Indrajeet A.; Kalshetti, Basavraj S.; Patil, Vikas B.; Mane, Shivshankar R.; Ghanwat, Anil A.
Abstract : We established the first use of thiophene integrated with a quinoxaline-benzimidazole unit for energy storage applications and delivered strategies for further developments in the performance of such materials. Abstract : New organic framework materials, namely, polyphenylquinoxaline (QOP ) and polyphenylquinoxaline-benzimidazole (QOP-BOP ) were designed using a high-temperature (>100 °C) polymerization reaction with different monomers, i.e., 2, 5-bis-[(4-benzoylcarbonyl)phenyl]-3-4 diphenyl thiophene (BbcPDT ), aromatic tetraamines and biphenyl dicarboxylic acid. TheQOP-BOP copolymer exhibited specific capacitance (SC) of 305 F g −1 at the current density of 2 A g −1 and 88% retention of its initial specific capacitance after 1000 cycles, which resulted in good cyclic stability. This work establishes the first use of thiophene integrated with quinoxaline-benzimidazole units for energy storage applications and provides strategies for further developments in the performance of such conjugated materials. Cyclic voltammetry, charge–discharge and electrochemical impedance techniques were used to evaluate the electrochemical parameters, which demonstrated their potential in future energy storage devices.